Active Control of Spontaneous Orientation Polarization of Tris(8‐hydroxyquinolinato)aluminum (Alq3) Films and Its Effect on Performance of Organic Light‐Emitting Diodes. (25th June 2021) - Esaki, Yu; Tanaka, Masaki; Matsushima, Toshinori; Adachi, Chihaya
Abstract: Vacuum‐deposited amorphous organic films with an anisotropic amorphous structure are known to exhibit spontaneous orientation polarization (SOP). In this study, amorphous structures of tris(8‐hydroxyquinolinato)aluminum (Alq3 ) films are controlled by substrate temperature ( T sub ) during vacuum deposition. The effect of density, molecular orientation, and SOP of Alq3 films on the performance of organic light‐emitting diodes (OLEDs) is comprehensively investigated. The SOP of Alq3 films is significant at low T sub and becomes weaker as T sub increases. The presence of SOP certainly improves electron injection from a metal cathode and, therefore, increases the current in OLEDs. External quantum efficiencies (EQEs) of OLEDs are increased by ≈40% when T sub for the Alq3 deposition is increased from 260 to 328 K. The increased EQEs are attributed to several factors, which include not only increased photoluminescence quantum yields and light outcoupling efficiencies but also suppressed singlet‐polaron annihilation originating from the reduced SOP. Operational stability of OLEDs is also affected by T sub and becomes the highest when Alq3 layers are vacuum‐deposited at T sub = 299 K. These findings indicate the importance of controlling organic amorphous structures and SOP in films to maximize OLED performance and contribute to a better understanding of working mechanisms of OLEDs. Abstract : Structural control of amorphous films by substrate temperature ( T sub ) during vacuum‐deposition enables an active tuning of spontaneous orientation polarization (SOP) in an organic semiconductor material, Alq3 . OLED performance is significantly influenced by SOP and induced charges on an organic/organic heterointerface. Suppression of singlet‐polaron annihilation has large contribution on EQE enhancement by ≈40%.